Penanaman Nilai-Nilai Agama Islam kepada Anak di Desa Mata Wolasi - Jaya Saputra; Marlina Gazali (Diniyah: Jurnal Pendidikan Dasar, 2022)
This study aims to find out how to instill religious values by parents to their children in the village of Mata Wolasi, Wolasi District, South Konawe Regency. This study employed qualitative research with a descriptive approach. The research informants were 9 residents of Mata Wolasi Village who were selected by purposive sampling technique. Research data were collected through observation, interviews, and documentation. The data was then analyzed through several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that there were four methods used by parents in passing on religious values to their children in Mata Wolasi Village, namely: habituation, example, advice and punishment. In teaching religious values to their children, mothers and fathers show the same role in the methods of habituation, advice, and punishment. However, fathers are more dominant in giving examples.Keywords: Internalization of religious values, children's character, parents' role